2005
DOI: 10.1097/01.mpg.0000168992.44428.fa
|View full text |Cite
|
Sign up to set email alerts
|

Breast Milk Fatty Acid Composition Is Associated with Development of Atopic Dermatitis in the Infant

Abstract: Breast milk rich in saturated and low in n-3 fatty acids may be a risk factor for atopic dermatitis in the infant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
48
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 28 publications
5
48
0
2
Order By: Relevance
“…Exclusive feeding of human milk (HM) is associated with attenuated, or delayed, development of food allergies (2). The long chain n-3 polyunsaturated fatty acid (PUFA) composition of HM is hypothesized to contribute to the protective effects of breast-feeding against allergy (3). Supporting the importance of these long chain polyunsaturated fats (LCP) in directing appropriate development of the immune system, recent studies demonstrate that supplementation during pregnancy with n-3 PUFA reduces the prevalence of allergic symptoms in high risk children (4,5).…”
mentioning
confidence: 99%
“…Exclusive feeding of human milk (HM) is associated with attenuated, or delayed, development of food allergies (2). The long chain n-3 polyunsaturated fatty acid (PUFA) composition of HM is hypothesized to contribute to the protective effects of breast-feeding against allergy (3). Supporting the importance of these long chain polyunsaturated fats (LCP) in directing appropriate development of the immune system, recent studies demonstrate that supplementation during pregnancy with n-3 PUFA reduces the prevalence of allergic symptoms in high risk children (4,5).…”
mentioning
confidence: 99%
“…One reason for the latter could be the trend to a lower content of fat in maternal breast milk of atopic children. Albeit no impact of maternal vitamin E intake -neither from diet nor from supplements -on its concentration in breast milk could be found (Hoppu et al 2005a), the same authors found a correlation between the levels of tocopherols in the blood of atopic mothers and their newborns at one month of age. While higher serum levels of the isoform α-tocopherol, which functions as vitamin E, were found in the infants, the predominantly antioxidant isoform γ-tocopherol was lower than in maternal serum (Hoppu et al 2005b).…”
Section: Dietary Antioxidants In Breast Milk: Vitamins C and Ementioning
confidence: 74%
“…The same study detected decreased levels of vitamin C and elevated levels of α-tocopherol in maternal breast milk, when children had a positive skin prick test at the age of one year (Hoppu et al 2005a). One reason for the latter could be the trend to a lower content of fat in maternal breast milk of atopic children.…”
Section: Dietary Antioxidants In Breast Milk: Vitamins C and Ementioning
confidence: 80%
See 1 more Smart Citation
“…Portanto, a presença dos AGPI-CL no leite ajuda no desenvolvimento do sistema imune da criança, atuando na produção de células T 37 . Isso é particularmente importante, já que a função do linfócito T é pouco desenvolvida no nascimento 38 .…”
Section: A Importância Dos áCidos Graxos No Leite Maternounclassified